Precipitation in the Nugget Zone of AA6061-T6 by Friction Stir Welding - Wang Tao (Science Faculty of Chiang Mai University, 2019)
Friction stir welding butt welded joints were fabricated successfully for heat-treated AA6061-T6 sheets with 5.85 mm thickness. The influences of welding parameters on structural features, precipitation kinetics and mechanical properties for the obtained welds were investigated by differential scanning calorimetry test, transmission electronic microscopy observation, electron backscattered diffraction and micro-hardness test. Results showed the hardness was influenced by the frequency of low angle gain boundary and precipitation phenomena. The rotation speed mainly has an effect on the frequency of low angle gain boundary, and the feeding speed mainly influences the evolution of precipitates. In addition to β' and β-Mg2Si phase in the nugget zone for all the joints, the u-phase was found with high feeding speed, and the TYPE-A phase with low feeding speed.